2014
DOI: 10.5455/2319-2003.ijbcp20140209
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profile of diabetic foot ulcers and its antibiotic susceptibility pattern in a teaching hospital, Gujarat

Abstract: Diabetes is a metabolic disorder of the endocrine system which plagues approximately 17 million people nationwide. Each year over 700,000 new cases are diagnosed; 12,000 to 14,000 of which are children, teenagers and young adults, while this life threatening disease can be controlled. Diabetes is often accompanied by serious complications, and still today there is no cure. 1 Foot ulceration and infection in diabetic patients is one of the major causes of morbidity, hospitalization and foot amputation. 2 This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
5
11
0
Order By: Relevance
“…Unlike Western countries reporting Gram-positive aerobes as predominant pathogens (Wang et al, 2010; Roberts and Simon, 2012), there has been a changing trend in the microorganisms causing DFI, with Gram-negative bacteria replacing Gram-positive bacteria in India (Ramakant et al, 2011; Umadevi et al, 2011). Interestingly, we have also observed the predominance of Gram-negative organisms in DFUs in our study and the same has also been reported by Mehta et al (2014) and Shankar et al (2005). However, previous studies reported the dominance of Gram-positive aerobes in diabetic foot infection (Mantey et al, 2000; Fejfarová et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike Western countries reporting Gram-positive aerobes as predominant pathogens (Wang et al, 2010; Roberts and Simon, 2012), there has been a changing trend in the microorganisms causing DFI, with Gram-negative bacteria replacing Gram-positive bacteria in India (Ramakant et al, 2011; Umadevi et al, 2011). Interestingly, we have also observed the predominance of Gram-negative organisms in DFUs in our study and the same has also been reported by Mehta et al (2014) and Shankar et al (2005). However, previous studies reported the dominance of Gram-positive aerobes in diabetic foot infection (Mantey et al, 2000; Fejfarová et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…All strains of S. aureus including MRSA were sensitive to vancomycin, which is similar to the findings of Reghu et al (2016), Kandati et al (2015), and Mehta et al (2014), but against the findings of Girish and Kumar (2011). …”
Section: Discussionsupporting
confidence: 88%
“…Diabetic foot is the most common, long-term and feared complication of diabetes and it is the principal cause of hospitalization among patients with diabetes (1). Diabetic foot is characterized by sensory, motor and autonomic neuropathy and peripheral vascular disease, which may lead to the development of ulceration, infection and gangrene (2).…”
Section: Introductionmentioning
confidence: 99%
“…6 But, as per Vaidehi et al, Klebsiella was second common isolate. 7 So, common organism isolated from wound was different in various studies. In our study, proteus was more common than staphylococcus, which is similar to the study of Gangania and Singh et al 8 In our study, we have found that Escherichia coli was less sensitive to cephalosporin and around 40% to 60% of the isolates were sensitive to quinolones, 60% of E. coli were sensitive to chloramphenicol, but they very much sensitive to imipenem.…”
Section: Discussionmentioning
confidence: 99%